A Concise Total Synthesis of Steroid Scaffolds via a Palladium-Catalyzed Dearomatization Cyclization - Huang, Zhangwei; Pan, Xianhua; Guo, Lei; Tang, Wenjun (Synlett, 2022)
A concise total synthesis to generate synthetically challenging steroids scaffolds is reported utilizing palladium-catalyzed dearomatization cyclization for the key cyclization step, enabling the divergent synthesis of 6,6,6,5-tetracyclic steroids cores through both ligand and reaction condition control. We have started from the simple starting materials 2,4,6-trihydroxybenzoic acid and 2-methylcyclopentane-1,3-dione to selectively generate complex steroid scaffolds in a 12-step operation.
Keywords: total synthesis; steroids scaffolds; palladium catalysis; dearomatization cyclization; 6,6,6,5-tetracyclic steroids